Design and synthesis of triptycene based fluorescent polymer with pendent triazole: Effect of functionality on host–guest interaction. Issue 22 (21st August 2017) - Mondal, Snehasish; Jana, Achintya; Bera, Ranajit; Das, Neeladri
ABSTRACT: Fluorescent materials have emerged as one of the promising candidates for chemical sensing due to their high sensitivity towards analytes that are relatively electron deficient such as nitroaromatics (NACs). Herein, four new 1, 2, 3‐triazole functionalized dibromo monomers (2‐5 ) have been synthesized. These dibromo monomers (2‐5 ) have been subsequently polymerized with 2, 6‐diethynyltriptycene (DET ) to yield four new ethynyl linked polymers (P2‐P5 ) with 1, 2, 3‐triazole pendent. These polymers are organosoluble, amorphous in nature and have high thermal stability [ T d  > 289 °C and high char yield (>73%) at 800 °C]. Interestingly these new polymers (P2‐P5 ) are highly fluorescent in solution ( Φ  = 0.37–0.43 in DCM) relative to the polymer (P1 ) that does not have the 1, 2, 3‐triazole motif as a pendent. The host–guest interaction between these polymers (P1‐P5 ) and electron deficient molecules (PA and C60 ) has been investigated. The Stern–Volmer quenching constant ( K SV ) data suggest that the interaction of picric acid and polymers increases significantly in presence of 1, 2, 3‐triazole linked pendent group whereas in case of C60, the K SV value decrease considerably in presence of 1, 2, 3‐triazole linked pendent. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 3725–3735 Abstract : Triptycene based and ethynyl linked nonconjugated fluorescent polymers with pendent 1, 2, 3‐triazole motif were synthesized. The objective was to develop highly fluorescent polymers with polar 1, 2, 3‐triazole groups yet with better organosolubility. The host–guest interaction of picric acid and polymers increases notably in presence of 1, 2, 3‐triazole linked pendent groups whereas in case of C60, K SV values decrease considerably in presence of these pendent groups.